Prediksi Kebangkrutan dengan Model Grover, Altaman Z-Score, Springate, Zmijewski, Olhson dan Fulmer: pada Perusahaan Pertambangan di Bursa Efek Indonesia (BEI) Tahun 2017 – 2021 - Wulansari, Siska; Nelvirita, Nelvirita (Universitas Negeri Padang, 2024)
The aim of this research is to determine (1) predictions of bankruptcy for mining companies listed on the Indonesia Stock Exchange using the Altman Z-Score, Springate, Fulmer, Ohlson, Zmijewski and Grover models from 2017 to 2021, and (2) to determine the level of accuracy six models in predicting bankruptcy. The sampling method used purposive sampling with several criteria which resulted in 37 samples of mining companies during 5 years of data observation. The research results show that, using the Altman model and the Ohlson model, it is estimated that 12 companies will experience bankruptcy. Springate model shows that 28 companies will go bankrupt. Meanwhile, the Fulmer and Zmijewski model predicts 31 companies will go bankrupt and the Grover model predicts 2 companies will go bankrupt. The Zmijewski model is a model that has the highest level of accuracy in predicting bankruptcy in mining companies, namely with an accuracy level of 98%.